Desert Royal - Sasson, Jean (London Bantam Books, 2000)
Continuing the life story of Princess Sultana of Saudi Arabia and her fight to relieve the oppression of the women in Muslim countries.
Originally published: London: Doubleday, 1999.
Keywords: Women--Social conditions -- Saudi Arabia -- Princesses